A qualitative inquiry on recovery needs and resources of individuals with intellectual disabilities labelled not criminally responsible. Issue 4 (16th September 2019) - Aga, Natalie; Vander Laenen, Freya; Vandevelde, Stijn; Vanderplasschen, Wouter
Abstract: Background: Recovery is a widely accepted paradigm in mental health care, whilst the correctional and forensic–psychiatric field is still searching for foundations for its implementation. Knowledge regarding recovery of persons with intellectual disabilities in secure contexts is limited. This study assesses recovery needs and resources among persons with intellectual disabilities labelled not criminally responsible and investigates the impact of the judicial label on recovery processes. Methods: A sample of 26 individuals was composed purposively, and in‐depth interviews were conducted. Recurrent themes were identified using thematic analysis. Results: Traditional recovery themes emerged from the narratives, next to aspects of recovery in a forensic or correctional context. However, the operationalization and proportional impact are specific for this sample. Conclusions: The social dimension overarches all other recovery dimensions. The integration of an explicit social rhetoric is imperative, including contextual, relational, interactional and societal dimensions. This offers pathways to reverse the traditional, paternalistic model of exclusion and classification.